Melhoria nos processos de pagamento em uma universidade federal - Lins, Lucivania Jacinto da Silva (2025)
Technological changes and shifts in the population profile have required public entities to alter the way they manage and provide services to keep pace with current dynamics. Using techniques typical of the private sector, government agencies seek to modernise their work routines to ensure good governance, transparency and credibility in their actions. In this context, this study proposes improvements to the payment process at the Federal University of Paraíba. To achieve this objective, an applied study was conducted, using a predominantly qualitative and descriptive approach, which employed bibliographic and documentary research, semistructured interviews and non-participant observation. The BPM approach, Value Added Analysis and the guidelines of ISO/TR 26122:2008 were also used to analyse and propose improvements to the process. The mapping of the current and suggested situations was developed using Bizagi software. The analyses performed on the collected material made it possible to detail the current process into 97 activities, of which 26 were identified as having no added value. The proposed new mapping resulted in a flow with 74 activities, after reorganising the steps and eliminating redundancies. The results indicate that the proposed improvements have the potential to increase organisational efficiency. This study contributes to the improvement of public sector actions and can be replicated in other institutions.